POLITICAL MODERNIZATION AND CIVIL SOCIETY: INTERACTION AND INFLUENCE ON THE DEMOCRATIC PROCESS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article explores the important interaction between political modernization andcivil society and its impact on the democratic process. Political modernization, as a key componentof modern political development, includes changes in institutions, structures and processes, as wellas in behavioral norms and values in the political system. Civil society, in turn, plays the role of anactive participant and controller of political processes, contributing to the creation of transparent,responsible and sustainable democratic institutions. The article examines how these two phenomena interact, in particular, how civil society can influence the process of political modernizationthrough active civic engagement, monitoring political reforms and advocating for the observanceof citizens’ rights and freedoms. Conversely, political modernization can help strengthen civilsociety by creating legislative and institutional mechanisms that promote civic engagement andparticipation.
Keywords: political modernization, civil society, democratic process, citizen participation, civil society institutions, strengthening of democracy, political reforms, activism, civic organizations, democratic development, civic activism.